Моделирование нестационарных режимов транспорта природного газа по многониточному магистральному газопроводу с учетом динамики работы запорной арматуры - Гусарова, И. Г.; Каминская, А. В. (ХНУРЭ, 2008)
The purpose of work is a mathematical design of the unstationary unisothermal modes of transport of natural gas in line sections of main gas pipelines taking into account the dynamics of work of constipation armature (valves, bolts, etc.) with a change speed of opening/closing of valves and evaluation of influencing of speed of blocking valves on distributing of parameters of gas stream on length of line sections of main gas pipelines in time.
Keywords: транспорт природного газа; магистральный газопровод